Competitiveness and Exports Sustainability of the Indonesian Natural Rubber - Rumbiati Kamaludin (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2018)
This paper examines Indonesian competitiveness in export of natural rubber commodities by employing set of revealed comparative advantage (RCA) and Export competitive index (ECI) with respect to global trade. The market structure that is formed on natural rubber commodities is calculated using Herfindahl Index and Concentration Ratio analysis tools shows the oligopoly-shaped market structure. Calculation of comparative advantage with RCA analysis shows that the four countries exporting natural rubber, namely Thailand, Indonesia, Malaysia and Vietnam each have a comparative advantage. Where Indonesia has a better comparative advantage than Thailand in the period 2011 to 2015. This result is different from the calculations made on competitive advantage (ECI) in which Indonesia's natural rubber commodities are not more competitive than Thailand